THE ROLE AND FUNCTION OF THE STUDENT PORTFOLIO IN THE PROCESS OF HIGHER EDUCATION - Rakhimov , Oktabr Dostkobilovich; Eshmirzaeva , Matluba Abdushukurovna (Educational Research in Universal Sciences, 2023)
The article presents the role of the student’s portfolio in the educational process of higher education, its content, and procedures for using it. Self-assessment based on developmental learning technology, the importance of the portfolio in the development of reflexive skills in the student is based on, the composition of the student portfolio and the requirements for its creation and management have been developed.